Dual-Phase β-Amyloid PET Captures Neuronal Injury and Amyloidosis in Corticobasal Syndrome - Schmitt, Julia; Palleis, Carla; Sauerbeck, Julia; Unterrainer, Marcus; Harris, Stefanie; Prix, Catharina; Weidinger, Endy; Katzdobler, Sabrina; Wagemann, Olivia; Danek, Adrian; Beyer, Leonie; Rauchmann, Boris-Stephan; et al. (Frontiers in Aging Neuroscience, 2021)
Objectives In recent years several 18F-labelled amyloid PET (Aβ-PET) tracers have been developed and have obtained clinical approval. There is evidence that Aβ-PET perfusion can provide surrogate information about neuronal injury in neurodegenerative diseases when compared to conventional blood flow and glucose metabolism assessment. However, this paradigm has not yet been tested in neurodegenerative disorders with cortical and subcortical affection. Therefore, we investigated the performance of early acquisition 18F-flutemetamol Aβ-PET in comparison to 18F-fluorodeoxyglucose (FDG)-PET in corticobasal syndrome (CBS). Methods Subjects with clinically possible or probable CBS were recruited within the prospective Activity of Cerebral Networks, Amyloid and Microglia in Aging and Alzheimer’s Disease (ActiGliA) observational study and all CBS cases with an available FDG-PET prior to Aβ-PET were selected. Aβ-PET was acquired 0-10 min p.i. (early-phase) and 90-110 min p.i. (late-phase) whereas FDG-PET was recorded statically from 30-50 min p.i. Semiquantitative regional values and asymmetry indices (AI) were compared between early-phase Aβ-PET and FDG-PET. Visual assessments of hypoperfusion and hypometabolism were compared between both methods. Late-phase Aβ-PET was evaluated visually for assessment of Aβ-positivity. Results Among 20 evaluated patients with CBS, 5 were Aβ-positive. Early-phase Aβ-PET and FDG-PET SUVr correlated highly in cortical (mean R = 0.86, range 0.77-0.92) and subcortical brain regions (mean R = 0.84, range 0.79-0.90). Strong asymmetry was observed in FDG-PET for the motor cortex (mean |AI| = 2.9%), the parietal cortex (mean |AI| = 2.9%), and the thalamus (mean |AI| = 5.5%), correlating well with AI of early-phase Aβ-PET (mean R = 0.87, range 0.62-0.98). Visual assessments of hypoperfusion and hypometabolism were highly congruent. Conclusions Early-phase Aβ-PET facilitates assessment of neuronal injury in CBS for cortical and subcortical areas. Known asymmetries in CBS are captured by this method, enabling assessment of Aβ-status and neuronal injury with a single radiation exposure at a single visit.